Luxembourg : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Luxembourg. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses that Luxembourg's growth prospects remain favorable, but downside risks arise from a weaker-than-expected global growth, a disorderly Brexit, changes in international tax rules, and a sharp tightening of global financial conditions. Domestically, rising real estate prices could exacerbate already elevated household indebtedness and increase affordability challenges. Fiscal policy should aim to maintain a strong fiscal position and preserve buffers. The government's plans, while appropriate, will result in a slightly expansionary budget in 2019. The cost and timeline of the planned measures over the medium term remain to be determined. Given risks ahead, including from potential changes in international taxation, Luxembourg should build on its strong fiscal record and preserve sizeable buffers. Structural policies should focus on addressing key gaps in the economy. Further reforms of the pension system are needed to ensure its sustainability, while considering intergenerational equity and trade-offs of various reform options.